Critical Discourse Analysis and the challenges and opportunities of social media. Issue 3 (3rd July 2018) - Bouvier, Gwen; Machin, David
ABSTRACT: Critical Discourse Analysis (CDA) is a particular strand of discourse analysis that focuses on the role of language in society and in political processes, traditionally targeting texts produced by elites and powerful institutions, such as news and political speeches. The aim is to reveal discourses buried in language used to maintain power and sustain existing social relations. However, since the internet and social media have come to define much of the way that we communicate, this brings numerous challenges and also opportunities for CDA. The relationship between text and ideology, and between the author and reader, appears to have changed. It is also clear that new methods are required for data collection, as content takes new forms and also moves away from running texts to language that is much more integrated with forms of design, images, and data. Also, new models are required to address how the technologies themselves come to shape the nature of content and discourse.